2016
DOI: 10.1002/ajim.22605
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of the effectiveness of occupational health and safety regulatory enforcement

Abstract: There is strong evidence that several OHS policy levers are effective in terms of reducing injuries and/or increasing compliance with legislation. This study adds to the evidence on OHS regulatory effectiveness from an earlier review. In addition to new evidence supporting previous study findings, it included new categories of evidence-compliance as an outcome, nature of enforcement, awareness campaigns, and smoke-free workplace legislation. Am. J. Ind. Med. 59:919-933, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 55 publications
2
64
0
1
Order By: Relevance
“…Other alternative designs for the evaluation of occupational health interventions have recently been proposed (83). Tompa et al (5) also reviewed the literature and used a "best evidence" synthesis to assess the strength of evidence. They concluded that there is strong evidence for several OHS policy levers in terms of reducing injuries and/or increasing compliance with legislation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other alternative designs for the evaluation of occupational health interventions have recently been proposed (83). Tompa et al (5) also reviewed the literature and used a "best evidence" synthesis to assess the strength of evidence. They concluded that there is strong evidence for several OHS policy levers in terms of reducing injuries and/or increasing compliance with legislation.…”
Section: Discussionmentioning
confidence: 99%
“…We used a quality appraisal protocol developed by Tompa et al (4,5) specifically for this type of review. It consists of ten items in two parts (study quality and policy lever relevance, see appendix, www.sjweh.fi/show_abstract.…”
Section: Quality Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is uncertainty at the effectiveness of consultation and awareness programs to prevent injuries over the long term. 710 …”
Section: Adoption Motivatorsmentioning
confidence: 99%